2021
DOI: 10.1089/thy.2020.0115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Weekly Servings of Cod for 16 Weeks in Pregnancy on Maternal Iodine Status and Infant Neurodevelopment: Mommy's Food, a Randomized-Controlled Trial

Abstract: Background: Mild-to-moderate iodine deficiency is still present in many countries, particularly in pregnant women. Observational studies suggest that mild-to-moderate iodine deficiency during pregnancy may be associated with impaired thyroid function and child neurodevelopment. Randomized-controlled food trials to increase iodine status are scarce. We assessed the impact of an increased intake of cod during pregnancy on maternal iodine status and infant neurodevelopment. Methods: In this randomized-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In contrast, the adverse influences of an unhealthy diet during pregnancy on the neurodevelopment of offspring remains after birth and even for long term. For instance, a randomized-controlled trial demonstrated that the maternal diet of two servings of cod per week during pregnancy might have adverse effects on infants' neurodevelopment [11]. A prospective birth cohort study found that maternal intake of excess folic acid supplements during pregnancy was associated with adverse psychomotor development in children after the first year of life [12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the adverse influences of an unhealthy diet during pregnancy on the neurodevelopment of offspring remains after birth and even for long term. For instance, a randomized-controlled trial demonstrated that the maternal diet of two servings of cod per week during pregnancy might have adverse effects on infants' neurodevelopment [11]. A prospective birth cohort study found that maternal intake of excess folic acid supplements during pregnancy was associated with adverse psychomotor development in children after the first year of life [12].…”
Section: Introductionmentioning
confidence: 99%
“…A moderate I deficiency is present in many countries, especially for pregnant women [ 48 ]. Due to this, there has been a focus on enriching meat or fish with I, for which seaweed could be a suitable source.…”
Section: Discussionmentioning
confidence: 99%
“…The current investigation is a secondary analysis from the study “Mommy's Food” (NCT02610959), which is a 2-armed randomized controlled trial (RCT) where pregnant women were randomly assigned to either receive dietary Atlantic cod ( Gadus morhua ) or continue with their habitual diet during the second and third trimesters of pregnancy (GWs 20–36) ( 26 ). The intervention increased the median UIC in the intervention group but had no effects on thyroid function ( 27 ). Therefore, in the current article, we wanted to explore potential associations between markers of iodine nutrition (UIC and iodine intake) and thyroid function tests in an observational design.…”
Section: Methodsmentioning
confidence: 99%
“…The study visits during pregnancy (GWs 18 and 36) and postpartum (3 and 6 mo) included the collection of biological samples (blood and urine samples) and questionnaires regarding demography, dietary intake, and supplement use. Further information about the study, including study design, power calculation, enrolment, and study procedures, has been published elsewhere ( 26 , 27 ).…”
Section: Methodsmentioning
confidence: 99%